The impact of fiscal decentralization, green innovation, and geopolitical risks on sustainable development - Nguyen , Thi Hong Ha; Tran , Thi Kim Oanh; Le , Hung Son (Journal of Finance - Marketing Research, 2025)
This study employs Bayesian regression to examine the impact of fiscal decentralization, green innovation, and geopolitical risks on sustainable development across 19 developed and 12 emerging economies over the period 2010–2022. The empirical results indicate that fiscal decentralization hinders sustainable development in emerging economies but promotes it in developed countries. Conversely, geopolitical risks act as a driver of sustainable development in emerging markets, while it negatively affects sustainable development in developed economies. Notably, green innovation consistently contributes to the enhancement of sustainable development across all countries examined. Based on these findings, the study proposes several policy implications tailored to the development context of each group of countries.